ANALISIS PENGARUH KOMPENSASI, KUALITAS HIDUP KERJA DAN DUKUNGAN SOSIAL TERHADAP KEINGINAN PINDAH KARYAWAN PADA PT. MANDAU BERLIAN SEJATI CABANG BALIKPAPAN - Agung Anarma; Sukisno S Riadi; Triana Fitriastuti (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Purpose of this study was to determine analysis of the influence Compensation, Quality Of Work life and Support Social to Turnover Intention employees on PT. Mandau Berlian Sejati a branch of Balikpapan. This Study secondary data from primary data in the questionnaire. Data were analyzed with regression models and use computer program SPSS.The result showed that Independent Variabel affect the Dependent variable with proven strong enough regression coefficient reached 72,8. Variable Compensation, Quality Of Work life and Support Social, Simultaneously significant affect the Turnover Intention. This is evidenced by the result of the F Test, Independent variables simultaneously affect the ependent variable with a significance level below 0,05. Partialy (their own) variable Compensation Significantly influence the Turnover Intention, Quality Of Work life variable significant affect the Turnover Intention, and Support Social variable significant affect the Turnover Intention employees on PT. Mandau Berlian Sejati a branch of Balikpapan.Â Keyword: Compensation ,Quality Of Work Life, Support Social and Turnover Intention